La Economía y la Estructura Empresarial del Departamento del Meta Frente al TLC con Europa – por Diego Morato (2014)
This paper will seek to raise academic and experiential discussion , regarding the different opinions of the authors cited , where positions are expressed as true experts in economy to the proposal, development and interaction of FTAs , with our country / region and department , with employers , unions and direct active players as producers, traders, exporters and importers who are the central focus of this theme that encompasses much of the competitiveness and productivity of domestic firms . This, taking as reference the current market conditions, the country's economic projection, the peace process, local and national governments, competition, challenges and opportunities. Discover, guide and clarify the serious questions of FTA approval and to support new market gains a developing nation with competitive disadvantages and exploit many comparative advantages, make more real the way to go. To investigate the capabilities and interest of the Colombian business community / regional and departmental reality facing balance imports and exports by sector in Colombia, showing figures to analyze and understand our role as observers and enter managers act as true changes cultural, political and economic where unity and general welfare takes precedence over the individual good identifying opportunities and challenges every day.